Evaluating the impact of prioritization of antiretroviral pre-exposure prophylaxis (PrEP) in New York City - Kessler, Jason (AIDS, 2014)
OBJECTIVE: To compare the value and effectiveness of different prioritization strategies of pre-exposure prophylaxis (PrEP) in New York City (NYC). DESIGN: Mathematical modeling utilized as clinical trial is not feasible. METHODS: Using a model accounting for both sexual and parenteral transmission of HIV we compare different prioritization strategies (PPS) for PrEP to two scenarios—no PrEP and PrEP for all susceptible at-risk individuals. The PPS included PrEP for all MSM, only high-risk MSM, high-risk heterosexuals, and injection drug users, and all combinations of these four strategies. Outcomes included HIV infections averted, and incremental cost effectiveness (per-infection averted) ratios. Initial assumptions regarding PrEP included a 44% reduction in HIV transmission, 50% uptake in the prioritized population and an annual cost per person of $9,762. Sensitivity analyses on key parameters were conducted. RESULTS: Prioritization to all MSM results in a 19% reduction in new HIV infections. Compared to PrEP for all persons at-risk this PPS retains 79% of the preventative effect at 15% of the total cost. PrEP prioritized to only high-risk MSM results in a reduction in new HIV infections of 15%. This PPS retains 60% of the preventative effect at 6% of the total cost. There are diminishing returns when PrEP utilization is expanded beyond this group. CONCLUSIONS: PrEP implementation is relatively cost-inefficient under our initial assumptions. Our results suggest that PrEP should first be promoted among MSM who are at particularly high-risk of HIV acquisition. Further expansion beyond this group may be cost-effective, but is unlikely to be cost-saving.